Analytical Evaluation of Dried Blood Spot and Rapid Diagnostic Test as a New Strategy for Serological Community Screening for Chronic Chagas Disease - Silgado, Aroa; Gual-Gonzalez, Lídia; Sánchez-Montalvá, Adrián; Oliveira-Souto, Inés; Goterris, Lidia; Serre-Delcor, Nuria; Esperalba, Juliana; Gomez-i-Prat, Jordi; Fernández-Naval, Candela; Molina, Israel; Pumarola, Tomas; Sulleiro, Elena (Frontiers in Cellular and Infection Microbiology, 2021)
Background Chagas disease is a public health problem not only in Latin America, but also in other regions, including Spain, due to migration movements. Conventional serological diagnosis requires an invasive sample (plasma or serum) and a well-equipped laboratory. To circumvent those limitations, blood samples dried on filter paper (DBS) or Rapid Diagnostic Test (RDT) could be a practical alternative to reference protocol for serological screening in epidemiological studies. We evaluated the usefulness of dried blood sampling and a rapid diagnostic test (Trypanosoma Detect™) for the detection of antibodies against T. cruzi for their use in community-based screening. Methodology/Principal Findings A total of 162 stored paired whole-blood and serum samples from Latin American migrants and 25 negative-control blood samples were included. Diagnosis of chronic Chagas disease was performed in serum according to WHO algorithms. Blood samples were retrospectively collected as dried spots and then analyzed using two different serological techniques, enzyme-linked immunosorbent assay (ELISA) and electrochemiluminescence immunoassay (E-CLIA). Whole-blood samples were also used to evaluate a rapid diagnostic test based on immunochromatography. A better correlation with conventional serum was observed in dried blood elutes using E-CLIA than ELISA (97% vs. 77% sensitivity, respectively). Both assays reported 100% specificity. The median cut-off index values of E-CLIA for dried blood were significantly lower than those for serum (138.1 vs. 243.3, P<0.05). The Trypanosoma Detect™ test presented a sensitivity and specificity of 89.6% and 100%, respectively. Conclusions The detection of antibodies against T. cruzi in dried blood samples shows a higher sensitivity when using E-CLIA compared with ELISA. Trypanosoma Detect™ is easier to use but has a lower sensitivity. Hence, we propose a sequential strategy based on performing the rapid test first, and a negative result will be confirmed by DBS-ECLIA for use in community Chagas disease screening programs.